2022
DOI: 10.1098/rsob.210379
|View full text |Cite
|
Sign up to set email alerts
|

Reversible bacteriophage resistance by shedding the bacterial cell wall

Abstract: Phages are highly abundant in the environment and pose a major threat for bacteria. Therefore, bacteria have evolved sophisticated defence systems to withstand phage attacks. Here, we describe a previously unknown mechanism by which mono- and diderm bacteria survive infection with diverse lytic phages. Phage exposure leads to a rapid and near-complete conversion of walled cells to a cell-wall-deficient state, which remains viable in osmoprotective conditions and can revert to the walled state. While shedding t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…3B and C ). This resembles our previously reported observations that described a phage-induced escape mechanism that allows the bacterial cell to shed its cell wall and thereby evade phage predation ( 12 , 19 ). By exposing these spherical cells to water, we observed that the majority of cells were lysed, which indicates that these are likely not spores but indeed cell wall-deficient cells as described in Ongenae et al ( 12 , 19 ) (Fig.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…3B and C ). This resembles our previously reported observations that described a phage-induced escape mechanism that allows the bacterial cell to shed its cell wall and thereby evade phage predation ( 12 , 19 ). By exposing these spherical cells to water, we observed that the majority of cells were lysed, which indicates that these are likely not spores but indeed cell wall-deficient cells as described in Ongenae et al ( 12 , 19 ) (Fig.…”
Section: Resultssupporting
confidence: 90%
“…The thin glass bottom ( 26 , 27 ), fixation of motile bacteria in a matrix, and barrier-free separation of bacteria and phages by the phaseguide allow for improved long-term imaging that can capture small details such as a change in bacterial cell shape. This is illustrated by the observation of the formation of cell wall-deficient cells in response to phage predation ( 12 ). Likely, this behavior went unnoticed previously due to the limited imaging quality possible with a 96-well plate setup.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, L-form research has mostly addressed their possible role as persisters in chronic or recurrent infections [16][17][18][19] . While it has been pointed out previously that L-forms or wall-deficient cells may also confer resistance to phage infection [20][21][22][23] , the biological relevance of this phenomenon remained elusive because no clear link between phage infection and L-form emergence has yet been demonstrated. Here we investigate the effects of phage infection on the emergence of bacterial L-forms, using Listeria monocytogenes and phage A006.…”
Section: L-form Escape Is Mediated By Endolysin Damagementioning
confidence: 99%